Changes of Nutrient Concentrations in the Western Baltic Sea in the Transition Between Inner Coastal Waters and the Central Basins: Time Series From 1995 to 2016 With Source Analysis - Kuss, Joachim; Nausch, Günther; Engelke, Clemens; Weber, Mario von; Lutterbeck, Hannah; Naumann, Michael; Waniek, Joanna J.; Schulz-Bull, Detlef E. (Frontiers in Earth Science, 2020)
Anthropogenic nitrogen input to the western Baltic Sea has continued to decline, by about 30% since 1995, whereas phosphorus input, after a strong decrease of 25% from 1995 to 2000, remained almost on the same level. Despite this development, the Arkona Sea and Belt Sea apparently show no strong changes of nutrient concentrations in the last two decades. In this study, we investigate the concentrations of nitrate, nitrite, ammonium, DIN (dissolved inorganic nitrogen), dissolved inorganic phosphorus (DIP), Total nitrogen (TN) and Total phosphorus (TP), as the substances of major concern in respect to the eutrophication of the Baltic Sea. To link open sea nutrient concentrations with nutrient supply by freshwater drain, we used nutrient versus salinity linear fits, including data from coastal waters obtained during regular German monitoring campaigns. Therefore, the data set was grouped according to differently sized areas to identify regional differences and was subsequently analyzed for four time intervals 1995-1999, 2000-2004, 2005-2009 and 2010-2016. By extrapolation to a salinity of “zero” we obtained hypothetical freshwater end-members of the different N and P parameters. Most of these end-members indicated a decline during the four time intervals, supporting a reduction of freshwater borne N and P supply to the western Baltic Sea. For the period 1995-1999 the freshwater end-members of TN were determined between 200 µM and 400 µM. This improved to a TN range between 150 µM and about 300 µM in 2010-2016. TP ranged from about 2.3 µM to 5.4 µM in 2010-2016 with previous values of slightly above 4 µM and up to almost 15 µM in the period 1995-1999. The end-members determined by our method would fulfill limnic-marine target values of the EU Water Framework Directive of TN = 186 µM and river-type specific target values of TP between 3-5 µM for some areas of the western Baltic Sea in recent years, because the method includes removal processes in the transition zone. Finally, the end-member values were compared to area specific averages of measured values at the limnic-marine transition point.